Nonlinear Coupled Dynamic Response of a Semi-submersible Platform - Kurian, V.J.; Yassir, M.E.A.; Harahap, I.S.H. (2010)
The dynamic behavior of a conventional semi-submersible was investigated both numerically and experimentally in regular and irregular waves. In the mathematical model, the dynamic equilibrium equationswere developed and solved in time domain using a common reference axis system fixed on the mean sea water level.The wave force calculations were based on the modified version of Morison Equation applied at the displaced position of the structure.Mooring system contribution to dynamic behavior was evaluated numerically using nonlinear catenary equations. The mooring stiffness matrix was evaluated interms of the mooring fairleader coordinates and spring constants. Experimentally, a twin hulled semi-submersible with a scale of 1:100 was tested in regular and irregular waves with the model oriented in the head, beam and quartering directions. The experimental measurements validated the accuracy of the numerical model. KEYWORDS:Equation of motion (EOM);Fast Fourier transformation (FFT);Response amplitude operator (RAO); Semisubmersible model; Time domain analysis; Wave basin testing.